2010
DOI: 10.5194/nhess-10-2547-2010
|View full text |Cite
|
Sign up to set email alerts
|

Performance of masonry buildings during the 20 and 27 December 2007 Bala (Ankara) earthquakes in Turkey

Abstract: Abstract. This paper evaluates the performance of masonry buildings during the 20 and 27 December 2007 Bala (Ankara) earthquakes. Bala is a township located 50 km southeast from Ankara city in Turkey. The majority of the buildings in the affected region are built in masonry. Most of masonry buildings were formed with random or coursed stone and mud brick walls without any reinforcement. Many of these buildings were damaged or had collapsed. The cracking and failure patterns of the buildings are examined and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…Failure mechanisms observed during the 2017 Ayvacık (Çanakkale) earthquake swarm were also observed in other recent moderate earthquakes in Bala (M L = 5.5), Dogubeyazıt (M L = 5.1), Dinar (M L = 5.9) and so on (Tezcan, 1996;Bayraktar et al, 2007;Adanur, 2010;Ural et al, 2012). Adanur (2010) showed that based on the investigations after the 20 and 27 December 2007 Bala (Ankara) earthquakes, masonry buildings were built in three types in the affected area: (1) stone masonry buildings with walls made of natural shaped stones, (2) stone masonry buildings with walls made of cut stones and (3) mixed ma-sonry buildings with walls made of masonry materials like stones and mud bricks, stones and bricks or stones and briquette. Overall, a total of 945 buildings were heavily damaged or collapsed in Bala.…”
Section: Damage Profilementioning
confidence: 56%
“…Failure mechanisms observed during the 2017 Ayvacık (Çanakkale) earthquake swarm were also observed in other recent moderate earthquakes in Bala (M L = 5.5), Dogubeyazıt (M L = 5.1), Dinar (M L = 5.9) and so on (Tezcan, 1996;Bayraktar et al, 2007;Adanur, 2010;Ural et al, 2012). Adanur (2010) showed that based on the investigations after the 20 and 27 December 2007 Bala (Ankara) earthquakes, masonry buildings were built in three types in the affected area: (1) stone masonry buildings with walls made of natural shaped stones, (2) stone masonry buildings with walls made of cut stones and (3) mixed ma-sonry buildings with walls made of masonry materials like stones and mud bricks, stones and bricks or stones and briquette. Overall, a total of 945 buildings were heavily damaged or collapsed in Bala.…”
Section: Damage Profilementioning
confidence: 56%
“…However, due to the low quality of construction this structure type has performed very poorly in recent and past earthquakes (Ali and Mohammad, 2006;Bothara and Brzev, 2011;Gupta et al, 2008;Kaushik et al, 2006;Murty, 2003;Naseer et al, 2010;Rai and Murthy, 2006, among others). The poor performance of stone masonry buildings have been observed also in other parts of the world (Adanur, 2010;Akkar et al, 2011;Gulkan et al, 1992;Ingham and Griffith, 2011;Spence, 2007a).…”
Section: Introductionmentioning
confidence: 82%
“…The strength of masonry under these conditions often depends on the bond between stone and mortar (or brick and mortar). This bond is often very poor when lime mortars or mud mortars are used [5]. Massive losses of both human lives and properties from the Nepal earthquake in 2015 demonstrate the need to strengthen masonry structures due to their poor seismic performance, as indicated by their inherent brittleness and low tensile strength [6].…”
Section: Introductionmentioning
confidence: 99%